2011
DOI: 10.1111/j.1600-0625.2011.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and differential expression of the skin-related chemokines CCL27 and CCL17 in psoriasis, atopic dermatitis and allergic contact dermatitis

Abstract: CCL27 and CCL17 are chemokines believed to be involved in the process of establishing the inflammatory infiltrate, characteristic for the various inflammatory skin diseases. The skinspecific CCL27 binds the chemokine receptor-10 (CCR10), and CCL17 is a chemokine receptor-4 (CCR4) ligand. The purpose of our study was to characterize the expression of CCL27 and CCL17 in the inflammatory skin diseases: psoriasis, atopic dermatitis (AD) and acute allergic contact dermatitis (ACD) induced in nickel-sensitive indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 36 publications
6
40
1
1
Order By: Relevance
“…In fact, while the upregulation of CCL27 and CCL17, a ligand for CCR4, was demonstrated in allergic dermatitis (Homey et al, 2002)(Moed et al, 2004)(Kanda et al, 2005)(Riis et al, 2011a), one recent report found a markedly decreased CCL27 expression in psoriatic lesions compared with non-lesional psoriatic skin and there was only a minor CCL17 mRNA increase in lesional psoriatic skin (Riis et al, 2011a). In addition, the expression of CCR4 was found on CCR10 + lymphocytes in atopic dermatitis skin but not in psoriasis skin (Vestergaard et al, 2003).…”
Section: Roles Of Ccr10/ligands In Regulation Of T Cell Response In Skinmentioning
confidence: 99%
“…In fact, while the upregulation of CCL27 and CCL17, a ligand for CCR4, was demonstrated in allergic dermatitis (Homey et al, 2002)(Moed et al, 2004)(Kanda et al, 2005)(Riis et al, 2011a), one recent report found a markedly decreased CCL27 expression in psoriatic lesions compared with non-lesional psoriatic skin and there was only a minor CCL17 mRNA increase in lesional psoriatic skin (Riis et al, 2011a). In addition, the expression of CCR4 was found on CCR10 + lymphocytes in atopic dermatitis skin but not in psoriasis skin (Vestergaard et al, 2003).…”
Section: Roles Of Ccr10/ligands In Regulation Of T Cell Response In Skinmentioning
confidence: 99%
“…Although there are hints that CCL27 is crucial for Th2 rather than for Th1-mediated diseases [18,19], its role for eczema as a Th2-dominant disease needs to be elucidated in more detail. However, the authors and others showed that CCL27 is found at lower levels in psoriasis compared with eczema [12,20,21]. Besides, IL17 is supposed to downregulate CCL27 expression [22], and also further cytokines overexpressed in psoriasis, such as INF-g and TNF-a, have a pivotal role in downregulating CCL27 expression at later stages of psoriatic plaques [23].…”
mentioning
confidence: 99%
“…Notably, Kamsteeg et al 57 analyzed patterns of several marker proteins to help differentiate inflammatory skin conditions including psoriasis, atopic dermatitis, allergic contact dermatitis, and irritant contact dermatitis. Through analysis of genetic signatures of skin biopsies via polymerase chain reaction, immunohistochemistry, and bioinformatics, Riis et al 58 found that neuron-specific Nel-like protein 2 exhibited strong induction in atopic dermatitis, whereas CCL17 and CXCL10 mRNA and protein were found in allergic contact dermatitis as compared with control subjects. Differences in expression of fast and slow acetylators of arylamine N-acetyltransferases have been seen between atopic versus allergic contact dermatitis, thus suggesting that N-acetylation polymorphisms could serve as genetic markers for atopic dermatitis.…”
Section: The Future: More Objective Criteria For Atopic Dermatitis?mentioning
confidence: 98%